The Effect Of The Stem Approach Aided By The Assemblr Edu Media On The Learning Outcomes Of Grade V Students - Suci Elsa Pratama; Waridah (Universitas Islam Ahmad dahlan, 2026)
The problem in this study is the low learning outcomes of IPAS in grade V students. This study uses a quantitative approach with a Pre-Experimental design of the One-Group Pretest-Posttest Design. The research sample amounted to 23 students who were determined using saturated sampling techniques. The research instrument was in the form of a multiple-choice test of 20 questions that had gone through a construct validity and reliability test with a Cronbach's Alpha coefficient of 0.877. Data analysis was carried out through the Shapiro–Wilk normality test and hypothesis test using a paired sample t-test with the help of SPSS version 25. The results showed that the average pretest score of 53.91 increased to 75.43 in the posttest, with a difference of 21.52 points. The results of the paired sample t-test showed a Sig. (2-tailed) value of 0.000 (< 0.05) H₀ was rejected and Hₐ was accepted, so there was a difference in learning outcomes before and after treatment. So, the conclusion is, the STEM approach assisted by Assemblr EDU media has an effect on improving the learning outcomes of grade V students of SDN 1 Ella Hilir